The expression `-8/sqrt 3 - 10/sqrt 14` has to be simplified.

`-8/sqrt 3 - 10/sqrt 14`

= `(-8*sqrt 3)/3 - (10*sqrt 14)/14`

= `(-8*14*sqrt 3 - 10*3*sqrt 14)/(14*3)`

= `(-112*sqrt 3 - 30*sqrt 14)/42`

= `(-56*sqrt 3 - 15*sqrt 14)/21`

**The expression**` -8/sqrt 3 - 10/sqrt 14 = (-56*sqrt 3 - 15*sqrt 14)/21`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.